FENOL, FLAVONOID, DAN AKTIVITAS ANTIOKSIDAN PADA EKSTRAK KULIT BATANG PULAI (Alstonia scholaris R.Br) - Zuraida; Sulistiyani; Dondin Sajuthi; Irma Herawati Suparto (Jurnal Penelitian Hasil Hutan, 2017)
Alstonia scholaris R.Br belongs to family Apocynaceae, is one of medicinal forest plant as traditional medicine to treat fever, malaria, cough with phlegm, diarrhea, diabetes, cholesterol-lowering, intestinal worms, acute rheumatism, ulcers, and hypertension. One of the causes of heart disease, atherosclerosis, and cancer is oxidative stress. The stress can be cured or reduced by taking antioxidant. Flavonoid, a phenol compound class, is one of the secondary plant metabolites that function as antioxidant. This paper determines total levels of phenol, flavonoid, and antioxidant activity of Alstonia *stem bark extract (Alstonia scholaris R. Br). Quantitative determination of total phenolics with the folin-ciocalteu method expressed as mg of gallic acid equivalent (GAE) per gram of extract, total flavonoids content by AlCl₃ method expressed as Quercetin equivalent (QE), and in vitro antioxidant activities with DPPH (2,2-diphenyl-1-picrylhydrazyl) method expressed in terms of IC₅₀ (inhibition concentration). Results show that extraction of three replicates in maceration with 96% ethanol yielded 4.19% filtrate. The total phenolic content was 51.50 mg GAE /g extract, while the total flavonoid content was 0.35 mg QE /g extract. IC₅₀ value of antioxidant activity assay of stem bark extract was 211.54 µg/mL.